2002
DOI: 10.1177/154405910208101210
|View full text |Cite
|
Sign up to set email alerts
|

Cathelicidin Antimicrobial Peptides are Expressed in Salivary Glands and Saliva

Abstract: The expression of antimicrobial peptides at epithelial surfaces such as skin, lung, and intestine is thought to provide protection against infection. Cathelicidin antimicrobial peptides are essential for the protection of skin against invasive bacterial infection. To determine if cathelicidins are also present in the oral cavity, we examined the expression of both mRNA and protein in mice and human saliva. The murine cathelicidin (CRAMP) was detected in the adult by reverse-transcription/polymerase chain-react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
137
2
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(146 citation statements)
references
References 33 publications
2
137
2
5
Order By: Relevance
“…In the human, LL37 was detected in saliva (Murakami et al, 2002). The results suggest localized expression of different antimicrobial peptides in salivary glands and ducts, similar to that of the gingiva (see above).…”
Section: Ll-37supporting
confidence: 53%
See 1 more Smart Citation
“…In the human, LL37 was detected in saliva (Murakami et al, 2002). The results suggest localized expression of different antimicrobial peptides in salivary glands and ducts, similar to that of the gingiva (see above).…”
Section: Ll-37supporting
confidence: 53%
“…The cathelicidin, LL-37, is expressed in epithelial cells especially following inflammatory stimulation, and both the protein and mRNA have been detected in human tongue and buccal mucosa (Frohm Nilsson et al, 1999) and saliva (Murakami et al, 2002). However, LL-37 detected in gingival epithelium by immunohistochemisty appeared to be the product of neutrophil migration through the tissue rather than the epithelial cells per se .…”
Section: Ll-37 and α-Defensinsmentioning
confidence: 99%
“…[7][8][9][10] Constitutive expression of antimicrobial peptides has previously been detected in various exocrine glands such as the human cathelicidin LL-37 in sweat glands, the cathelicidin CRAMP in murine salivary glands and ␤-defensins in human salivary glands. [21][22][23] Expression of human ␤-defensin-2 (hBD-2) mRNA in mammary glands was reported by Bals et al 24 in 1998 and recently other groups have found constitutive hBD-1 expression in mammary glandular tissue of nonlactating women as well as in breast tissue during lactation and in breast milk. 25,26 Our finding that hCAP18/LL-37 is expressed in breast cancer cells is novel.…”
Section: Discussionmentioning
confidence: 93%
“…Neutrophils are a particularly rich source of cathelicidins in a variety of species. In humans, cathelicidins have also been found to be expressed in several other tissues, including the testis (Agerberth et al 1995;Malm et al 2000), squamous epithelia (Frohm Nilsson et al 1999;Nizet et al 2001), airway epithelia (Bals et al 1998), sweat glands (Murakami et al 2002b), salivary glands (Murakami et al 2002a) and colon (Hase et al 2002). Cathelicidins have a wide spectrum of antimicrobial activity and have been shown to be active against Gram-negative and Grampositive bacteria (Travis et al 2000), fungi (Shin et al 2000) and enveloped viruses (Tamamura et al 1995).…”
Section: Introductionmentioning
confidence: 99%